Peranan Ekonomi Digital Terhadap Perekonomian Di Provinsi Kalimantan Selatan: Analisis Input-Output - Siti Fatimah; Muhammad Handry Imansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the role of the digital economy in the formation of sectoral output, intermediate demand and final demand for the Province of South Kalimantan, to determine the forward linkage and backward linkage of the digital economy to other economic sectors and to determine the value of the multiplier (multiplier) the digital economy in increasing income, employment and output creation in the economy. This study uses an analysis tool for the 2016 South Kalimantan input-output model, with 52 industrial sectors.There are 3 methods used, namely Contribution Analysis, Linkage Analysis and Multiplier Analysis. The results show that the contribution of the digital economy to output, intermediate demand and final demand is only around 1-6 percent, this contribution is relatively small compared to the contribution of other sectors, this is because there are several sectors that are included in the measurement of the digital economy that have not developed in Kalimantan. South. The forward linkage of the digital economy sector gives a value of 2,017, while the backward linkage of the digital economy is 1.375. The high forward linkage of the digital economy sector compared to the backward linkage indicates that the digital economy plays a role in attracting and developing the downstream sector compared to the upstream sector. The digital economy sector income multiplier is 0.199, the digital economy sector job multiplier is 0.004. The digital economy sector's output multiplier of 2,017 is a relatively small number, indicating that the ability of the digital economy to drive income growth and output creation is relatively low.